In-depth analysis of high-speed, cold neutron imaging of air-water two-phase flows. (April 2019) - Zboray, R.; Trtik, P.
Abstract: We have recently published first results of high frame rate cold neutron radiography of air-water two-phase flows in a bubbler. We have demonstrated imaging rates up to 800 frames per second by using a high-efficiency scintillator screen in combination with the highest available flux on the ICON beam line of the SINQ continuous spallation source and an imaging detector based on a high-speed sCMOS camera. Here we present an in-depth analysis of the experiments taken at several air injection rates and at different imaging rates. The dynamically resolved gas fraction distribution is investigated together with the bubble size and the instantaneous gas interfacial velocity distributions. The latter is evaluated using the optical flow (OF) method. The analysis presented here can be useful not only for analyzing dynamic neutron imaging sequences of multi-phase flows but of multi-component, mixing systems in general. Highlights: High-speed, cold neutron radiography of adiabatic air-water two-phase flow. 800 fps frame rate is achieved. Quantitative evaluation of two-phase parameters: instantaneous gas fraction distribution, bubble-size distribution. Optical flow method for gas interface velocity distributions.